Experiences of physical activity during pregnancy in Danish nulliparous women with a physically active life before pregnancy. A qualitative study - Damm Peter P; Kjaergaard Hanne; Hegaard Hanne K; Petersson Kerstin; Dykes Anna-Karin (BMC, 2010)
Abstract Background National guidelines recommend that healthy pregnant women take 30 minutes or more of moderate exercise a day. Most women reduce the level of physical activity during pregnancy but only a few studies of women's experiences of physical activity during pregnancy exist. The aim of the present study was to elucidate experiences and views of leisure time physical activity during pregnancy in nulliparous women who were physically active prior to their pregnancy. Methods A qualitative study was conducted by means of personal interviews. Nineteen women, all with a moderate pre-pregnancy level of physical activity but with different levels of physical activity during pregnancy, participated in the study. Content analysis was applied. Results In the analyses of experiences and views of physical activities during pregnancy, four categories and nine sub-categories were developed: Physical activity as a lifestyle (Habit and Desire to continue), Body awareness (Pregnancy-related discomfort, Having a complicated pregnancy and A growing body), Carefulness (Feelings of worry and Balancing worry and sense of security) and Sense of benefit (Feelings of happiness and Physical well-being). Conclusion As other studies have also shown, women find that the discomfort and complications associated with pregnancy, the growing body, and a sense of insecurity with physical activity are barriers to maintaining former levels of physical activity. This study adds a new perspective by describing women's perceptions of these barriers and of overcoming them - thus, when pregnant, the majority of the women do not cease to be physically active but continue to be so. Barriers are overcome by applying one's own experience, looking to role models, mirroring the activities of other pregnant women and following the advice of experts (midwives/physiotherapists). Women then continue to be physically active during pregnancy, most often to a lesser extent or in alternative activities, and derive considerable enjoyment and physical well-being from this.